Leaving no one behind: Supporting women, poor people, and indigenous people in wheat-maize innovations in Bangladesh - Farnworth, Cathy Rozel; Jafry, Tahseen; Rahman, S.; Badstue, Lone B. (International Maize and Wheat Improvement Center, 2018)
This guidance note for scientists and research teams acknowledges the complexity of marginalization processes and provides recommendations for making sure no one is left behind. It draws on GENNOVATE findings from a community in Bangladesh where the indigenous Santals, Bengali Muslims, and Hindus live and work together.